Evaluasi Program Pendidikan dan Pelatihan Bidang Manajemen Terhadap Peningkatan Kinerja Organisasi Oleh Badan Pengembangan Sumber Daya Manusia (BPSDM) Kementrian Pekerjaan Umum dan Perumahan Rakyat Republik Indonesia (PUPR-RI) - A. Susanti; T.C. Kurniatun (Pascasarjana Universitas Pendidikan Ganesha, 2022)
This study aims to 1) develop an evaluation instrument for post-training management in the field of management; 2) measuring the impact/benefit of the management trainings that have been conducted using the evaluation instruments that have been prepared; 3) obtain suggestions/recommendations for follow-up from the evaluation results of post-management training. The research was conducted in Makassar City, Medan City, Surabaya City, and DKI Jakarta. This study uses a quantitative and qualitative approach. The population in this study were alumni, direct supervisors, and colleagues from training alumni. The sampling technique is done randomly. Data were collected using questionnaires, documentation and interviews. Quantitative data analysis used the percentage of WMS and correlation with Partial Least Square (PLS), while the qualitative data used NVIVO 12. The results showed that most of the training alumni agreed that after attending the training, starting from leadership management, general management and construction management, the training alumni experienced changes. better work behavior. In addition, most of the alumni of the training agreed that after attending the training there was an increase in work that had a positive impact on organizational performance.